Model of Boundary Deposition Curves for Polydisperse Suspension Sedimentation in Flow-through Systems - Bakhyt Tazhibayeva; Arnold Brener; Leyla Musabekova; Vladimir Golubev; Zagira Kobeyeva; Altynay Yunussova (Chemical Engineering Transactions)
The novel model of sedimentation of polydisperse suspensions have been submitted. The model is devoted to describing the process of sedimentation of a polydisperse suspension in a flow-through systems. A concept for calculating the distribution of the dispersed phase in the flow leaving the apparatus based on a new methodology of boundary deposition curves has been developed. The developed model is allowing for calculating the evolution of the sedimentation front position and the sediment surface both along the height of the vessel and along longitudinal coordinate of the through-flowing apparatuses. An expressions and computer code for calculating the evolution of the sedimentation fronts have been developed, that is of importance for calculating the kinetics of sedimentation of polydisperse suspensions in nature and industrial flow-through devices. Using the approach of boundary deposition curves, a simple and effective method for calculating changes in the fractional composition of a suspension at the outlet of a flow region has been proposed.